Origin and implications of the low-Fe igneous series at Buldir Island, western Aleutian arc - Gene M. Yogodzinski; Shawn Arndt; Ryan Waldman; Michael Bizimis; Jeffrey Vervoort; Kenneth W. W. Sims (Contributions to Mineralogy and Petrology, 2026)
Volcanic whole-rock compositions from Buldir Island define a highly calc-alkaline (low-Fe) igneous series, with molar Mg/Mg + Fe* (total iron Mg#) mostly > 0.60; SiO 2 from 50–64 wt.%; and distinctly low FeO*, CaO, CaO/Al 2 O 3 , and FeO*/Al 2 O 3 relative to MgO. Many Buldir samples have trace element characteristics similar to western Aleutian seafloor lavas along upward curving trends of increasing Sr and Sr/Y with increasing SiO 2 and decreasing MgO. Least radiogenic Sr in andesites only (57–62 wt.% SiO 2 with 87 Sr/ 86 Sr ~ 0.7029) requires a key role for source mixing in the origin of the low-Fe series at Buldir. Andesites and dacites falling outside these source mixing trends show evidence of fractional crystallization interpreted to be a late-stage (over-printing) effect. Partitioning data indicate that heavy REEs will behave compatibly in amphibole-saturated melts evolving at temperatures < 1000 °C. However, recent hydrous and high fO 2 experiments show that Buldir melts with more than 4–5 wt.% MgO were unlikely to have reached amphibole saturation and cannot explain the decline in Yb concentrations starting at >9 wt.% MgO. Distinctive reverse sigmoidal (backward-S) REE pattern shapes in Buldir samples are also unlikely to be products of amphibole removal from evolving liquids and are instead interpreted to reflect melting of a light REE-depleted MORB source under eclogite conditions followed by interaction of the resulting hydrous-felsic slab melt with mantle peridotite upon ascent. Published pMELTS simulations and experimental observations indicate this style of melt-rock reaction will also create low FeO* and CaO in primitive (high-Mg#) melts over a wide range of SiO 2 and MgO, as observed in Buldir and western Aleutian seafloor datasets. The implication is that distinctive aspects of low-Fe calc-alkalinity in most Buldir samples with SiO 2 from 50 to 62% are created at sub-MOHO depths where cool-hydrous-siliceous partial melts of subducted-eclogitized MORB rise, decompress, and undergo thermal-chemical exchange with depleted peridotite that is hotter by hundreds of °C.

The Maskelyne irregular mare patch as interpreted with lunar optical data, including Danuri polarimetric measurements - Yuriy Shkuratov; Vadym Kaydash; James Head; Kilho Baek; Sungsoo S. Kim; Le Qiao; Sergey Velichko; Yehor Surkov; Nickolay Opanasenko; Minsup Jeong; Young-Jun Choi; Chae Kyung Sim; et al. (Icarus, 2026)

Marine clean-up dives remove more than just marine litter - Tokea G. Payton; Randi J. Sims; Lauren T. Bulik; Michael J. Childress (Marine Pollution Bulletin, 2026)

Distribution and taxonomic composition of leptocephali and hydrographic structure from New Zealand to the South Equatorial Current - Michael J. Miller; Shun Watanabe; Robert Schabetsberger; Nioka Behan-Kitto; Grace F. Cawley; Niamh Smith; Alisha M. Gill; Alexandre Che-Pelicier; Juliet E. Saul; Abigail Sim; Therese C. Miller; Sajini Dissanayake; et al. (Regional Studies in Marine Science, 2026)

Goals and trends in space exploration: An overview of the panel on exploration sessions at the committee on space research general assembly 2024 - André Galli; Heather Smith; Michel Blanc; Bernard Foing; Hélène Boithias; Scott J. Bolton; Soyoung Chung; Athena Coustenis; Eric Dautriat; Jean-Pierre de Vera; Peter Doran; François Dubrulle; et al. (Life Sciences in Space Research, 2026)

Integration of carbon nanotubes for MEMS and flexible electronics: Advances in fabrication and applications - Kyubin Bae; Sangjun Sim; Hyunjun Han; Michael Cullinan; Jongbaeg Kim (Chemical Engineering Journal, 2026)

Occurrence and Ecotoxicological Risks of Pharmaceuticals and Illicit Drugs in Effluent and Unsheltered Homelessness-Impacted River Systems - Douglas B. Sims; Joshua R. Monk; Desta Woldetsadik; Andressa C. Buch; Amanda C. Hudson; Mark C. Garner; Joseph Piacentini; Christopher Cohu; Chris S. Duvall; Jasmine Krause; Meaghan E. Hickey; Matthew Glazewski; et al. (Archives of Environmental Contamination and Toxicology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Characterization of the surface of the Ina irregular Mare patch: A synthesis of lunar optical data, including Danuri polarimetric measurements - Yuriy Shkuratov; Vadym Kaydash; James Head; Kilho Baek; Sungsoo S. Kim; Nickolay Opanasenko; Yehor Surkov; Minsup Jeong; Young-Jun Choi; Chae Kyung Sim; Dukhang Lee; Michael Kreslavsky; et al. (Icarus, 2026)

Does your job really matter? Job-specific cancer incidence among a cohort coal mine workers in Queensland, Australia - Deborah Catherine Glass; Stella May Gwini; Anthony Del Monaco; Lin Fritschi; Michael J. Abramson; Malcolm Ross Sim; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2026)
Purpose Globally, coal production exposes millions of workers to coal mine dust. This study aimed to measure overall and site specific cancer incidence among coal mine workers (CMW) who performed different types of work. Methods A retrospective cohort of CMW in Queensland, Australia, was assembled using health assessment records from 1992. CMW were grouped by job type and then into Work Categories and linked to the Australian Cancer Database up to 2016. Standardized cancer incidence ratios (SIR) and relative cancer incidence ratios (aRIR) within the cohort, adjusted for age, era, and smoking status, were calculated for men and women with Poisson regression. Results There were 5,568 cancers diagnosed among 146,553 men and 396 in 19,927 women. The overall cancer risk was comparable to that of the general population for most Work Categories. The risk of lung cancer was higher for male Production (SIR 123, 95% Confidence Interval [CI] 107–142; adjusted Relative incidence Ratio (aRIR) (adjusted for era, age and smoking status) 1.23, 95%CI 0.99-1.52) and Construction workers (SIR 189, 95%CI 31–272; aRIR 1.78, 95%CI 1.20–2.62) when compared with the Australian population and within the cohort after adjusting for smoking. Laryngeal cancer was increased in Production workers (SIR 145, 95%CI 100–212). Conclusions Increased rates of lung and laryngeal cancers were identified for male Production workers and lung cancer for Construction workers. These could be related to mine workplace exposures such as silica and diesel engine exhaust.

Genomic analysis of Vanessa tameamea, the threatened Hawaiian endemic butterfly, reveals population genetic structure relevant to conservation efforts - Haley E. Arnold; Julian R. Dupuis; Daniel Rubinoff; William P. Haines; Michael San Jose; Renee L. Corpuz; Angela N. Kauwe; Tyler J. Simmonds; Scott M. Geib; Sheina B. Sim (Conservation Genetics, 2025)
Patterns of divergence and speciation on islands have long been of interest in the broader study of evolution. Hawaiʻi’s endemic Kamehameha butterfly ( Vanessa tameamea ) is experiencing population decline, but because of its high vagility and assumed genetic homogeneity as a species, its population structure has not been investigated. To evaluate V. tameamea genetic variation across the Hawaiian Islands, we assembled a reference quality genome assembly for the species using HiFi and HiC reads and performed range-wide population genetic analyses using ddRAD sequencing data. A discriminant analysis of principal components (DAPC) revealed that, contrary to prior assumptions, V. tameamea populations appear to be diverging based on geography, in a pattern similar to other native Hawaiian terrestrial arthropods. Specifically, through demographic history analyses, we find that the distinct population on Kauaʻi is likely to be ancestral, the central islands of Maui, Molokaʻi, and Oʻahu comprise another population, and Hawaiʻi Island forms a third population, with likely more gene exchange with the central islands. Finally, we investigate the SNPs driving differences between groups and find that many are associated with genes that may be relevant to local adaptation to environmental chemicals such as host plant defenses or chemicals introduced by human activity, notably to do with metabolism and detoxification. While much field work remains to investigate any cryptic or phenotypic patterns as well as quantify effective migration, we hope that this work will inform refinement of conservation plans for one of Hawaiʻi’s two native butterflies.

Genomic infrastructure for cetacean research and conservation: reference genomes for eight families spanning the cetacean tree of life - Phillip A. Morin; Bernhard Bein; Chiara Bortoluzzi; Yury V. Bukhman; Taylor Hains; Dorothea Heimeier; Marcela Uliano-Silva; Dominic E. Absolon; Linelle Abueg; Jessica Antosiewicz-Bourget; Jennifer R. Balacco; Robert K. Bonde; et al. (Frontiers in Marine Science, 2025)
Reference genomes from representative species across families provide the critical infrastructure for research and conservation. The Cetacean Genomes Project (CGP) began in early 2020 to facilitate the generation of near error-free, chromosome-resolved reference genomes for all cetacean species. Towards that goal, and using the methods, goals and genome assembly quality standards of the Vertebrate Genomes Project (VGP), we generated 13 new reference genomes across eight of the 14 cetacean families. Additionally, we summarize the genome assembly characteristics for 18 species, including these newly-generated and five published genome assemblies that meet the completeness and quality standards. We infer ancestral linkage groups (ALG) for cetaceans, showing that the ancestral karyotype of 22 ALGs is largely conserved in extant species, except for Ziphiidae, and for Balaenidae and Kogiidae, which exhibit similar independent fusions. Gene annotation, characterization of historical demography, heterozygosity and runs of homozygosity (ROH) reveal important information for conservation applications. By comparing the new reference genomes to previous draft assemblies, we show that the reference genomes have enhanced characteristics that will support and promote scientific research. Specifically, the genomes improve resolution and characterization of repetitive elements, provide validation (or exclusion) of genes linked to complex traits, and allow more complete characterization of gene regions such as the highly complex Major Histocompatibility Complex (MHC) Class I and II gene clusters that are important for population health.

Life-cycle analysis of offshore macroalgae production systems in the United States - Hoyoung Kwon; Troy R. Hawkins; George G. Zaimes; Javier Infante; Hauke L. Kite-Powell; Michael S. Stekoll; Loretta Roberson; Beth Zotter; Simona Augyte; Greg Rocheleau; Neil Sims (Algal Research, 2024)

Abundance, patterns, and taxa associations of anthropogenic marine debris on reefs in the middle Florida Keys - Tokea G. Payton; Randi J. Sims; Michael J. Childress (Frontiers in Marine Science, 2024)
The Florida Keys reef tract has rapidly shifted from a structurally complex, hard coral-dominated reef to a less rugose, soft coral-dominated reef. This transition has been facilitated by persistent anthropogenic stressors including recreational and commercial fishing and increased anthropogenic marine debris. During the summers of 2020–2022, benthic censuses were conducted to identify substrate and marine debris composition for 30 reefs in the middle Florida Keys. Inshore reefs contained higher rugosity, coral cover, and marine debris abundance primarily comprised of monofilament and rope from fishing traps. Plastic items (e.g., ropes and monofilament) overall had the highest species diversity. Additionally, marine debris appears to promote turf algae growth on inshore reefs. While is it not yet possible to determine if this pattern of high debris nearshore is due to proximity to onshore debris sources, accumulation due to higher rugosity snagging debris, or increased debris removal efforts offshore, these differences in marine debris types and abundances suggest variability in potential impacts of debris on marine biota on inshore versus offshore reefs. Therefore, the differential use of marine debris by associated biota should be considered in marine debris management practices.

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Pea aphid odorant-binding protein ApisOBP6 discriminates between aphid sex pheromone components, aphid alarm pheromone and a host plant volatile - Cassie Sims; Michael A. Birkett; Neil J. Oldham; Robert A. Stockman; David M. Withall (Insect Biochemistry and Molecular Biology, 2023)

Long-term impact of the 2014 Hazelwood coal mine fire on emergency department presentations in Australia - Catherine L. Smith; Caroline X. Gao; Rongbin Xu; Jillian F. Ikin; Christina Dimitriadis; Matthew TC. Carroll; Malcolm R. Sim; Dion Stub; Tyler J. Lane; Michael J. Abramson; Yuming Guo (Environmental Research, 2023)

Food allergen recalls in the United Kingdom: A critical analysis of reported recalls from 2016 to 2021 - Sim Ray Yue; Rajeev Shrivastava; Katrina Campbell; Michael John Walker (Food Control, 2023)

Global-Scale Environmental Niche and Habitat of Blue Shark (Prionace glauca) by Size and Sex: A Pivotal Step to Improving Stock Management - Jean-Noël Druon; Steven Campana; Frederic Vandeperre; Fábio H. V. Hazin; Heather Bowlby; Rui Coelho; Nuno Queiroz; Fabrizio Serena; Francisco Abascal; Dimitrios Damalas; Michael Musyl; Jon Lopez; et al. (Frontiers in Marine Science, 2022)
Blue shark ( Prionace glauca ) is amongst the most abundant shark species in international trade, however this highly migratory species has little effective management and the need for spatio-temporal strategies increases, possibly involving the most vulnerable stage or sex classes. We combined 265,595 blue shark observations (capture or satellite tag) with environmental data to present the first global-scale analysis of species’ habitat preferences for five size and sex classes (small juveniles, large juvenile males and females, adult males and females). We leveraged the understanding of blue shark biotic environmental associations to develop two indicators of foraging location: productivity fronts in mesotrophic areas and mesopelagic micronekton in oligotrophic environments. Temperature (at surface and mixed layer depth plus 100 m) and sea surface height anomaly were used to exclude unsuitable abiotic environments. To capture the horizontal and vertical extent of thermal habitat for the blue shark, we defined the temperature niche relative to both sea surface temperature ( SST ) and the temperature 100 m below the mixed layer depth ( T mld+100 ). We show that the lifetime foraging niche incorporates highly diverse biotic and abiotic conditions: the blue shark tends to shift from mesotrophic and temperate surface waters during juvenile stages to more oligotrophic and warm surface waters for adults. However, low productivity limits all classes of blue shark habitat in the tropical western North Atlantic, and both low productivity and warm temperatures limit habitat in most of the equatorial Indian Ocean (except for the adult males) and tropical eastern Pacific. Large females tend to have greater habitat overlap with small juveniles than large males, more defined by temperature than productivity preferences. In particular, large juvenile females tend to extend their range into higher latitudes than large males, likely due to greater tolerance to relatively cold waters. Large juvenile and adult females also seem to avoid areas with intermediate SST (~21.7-24.0°C), resulting in separation from large males mostly in the tropical and temperate latitudes in the cold and warm seasons, respectively. The habitat requirements of sensitive size- and sex-specific stages to blue shark population dynamics are essential in management to improve conservation of this near-threatened species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Corrigendum: On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)

On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)
Terrestrial runoff can negatively impact marine ecosystems through stressors including excess nutrients, freshwater, sediments, and contaminants. Severe storms, which are increasing with global climate change, generate massive inputs of runoff over short timescales (hours to days); such runoff impacted offshore reefs in the northwest Gulf of Mexico (NW GoM) following severe storms in 2016 and 2017. Several weeks after coastal flooding from these events, NW GoM reef corals, sponges, and other benthic invertebrates ∼185 km offshore experienced mortality (2016 only) and/or sub-lethal stress (both years). To assess the impact of storm-derived runoff on reef filter feeders, we characterized the bacterial communities of two sponges, Agelas clathrodes and Xestospongia muta , from offshore reefs during periods of sub-lethal stress and no stress over a three-year period (2016—2018). Sponge-associated and seawater-associated bacterial communities were altered during both flood years. Additionally, we found evidence of wastewater contamination (based on 16S rRNA gene libraries and quantitative PCR) in offshore sponge samples, but not in seawater samples, following these flood years. Signs of wastewater contamination were absent during the no-flood year. We show that flood events from severe storms have the capacity to reach offshore reef ecosystems and impact resident benthic organisms. Such impacts are most readily detected if baseline data on organismal physiology and associated microbiome composition are available. This highlights the need for molecular and microbial time series of benthic organisms in near- and offshore reef ecosystems, and the continued mitigation of stormwater runoff and climate change impacts.

Life cycle assessment applying planetary and regional boundaries to the process level: a model case study - Anders Bjørn; Sarah Sim; Henry King; Laure Patouillard; Manuele Margni; Michael Zwicky Hauschild; Morten Ryberg (The International Journal of Life Cycle Assessment, 2020)

Plasma Vitellogenin Reveals Potential Seasonal Estrogenicity in Fish from On-Site Wastewater Treatment Systems in Semi-Arid Streams Influenced by Snowmelt - Marco E. Franco; Kevin M. Stroski; Jaylen L. Sims; S. Rebekah Burket; Craig Ashcroft; Michael Luers; Bryan W. Brooks; Ramon Lavado (Bulletin of Environmental Contamination and Toxicology, 2020)

Total body irradiation in Australia and New Zealand: results of a practice survey - Lotte S. Fog; Andrew Wirth; Michael MacManus; Simon Downes; Michael Grace; Alicia Moggré; Koki Mugabe; Gabor Neveri; Lisa Nourbehesht; Vanessa Panettieri; Dane Pope; Lucy Sim; et al. (Physical and Engineering Sciences in Medicine, 2020)

Overhauling Ocean Spatial Planning to Improve Marine Megafauna Conservation - Ana Micaela Martins Sequeira; Graeme Clive Hays; David W. Sims; Víctor M. Eguíluz; Jorge P. Rodríguez; Michelle R. Heupel; Rob Harcourt; Hannah Calich; Nuno Queiroz; Daniel Paul Costa; Juan Fernández-Gracia; Luciana C. Ferreira; et al. (Frontiers in Marine Science, 2019)

Impacts of consecutive bleaching events and local algal abundance on transplanted coral colonies in the Florida Keys - Kylie M. Smith; Tokea G. Payton; Randi J. Sims; Caroline S. Stroud; Reanna C. Jeanes; Taylor B. Hyatt; Michael J. Childress (Coral Reefs, 2019)

Transpacific coalescent pathways of coconut rhinoceros beetle biotypes: Resistance to biological control catalyses resurgence of an old pest - Jonathan Bradley Reil; Camiel Doorenweerd; Michael San Jose; Sheina B. Sim; Scott M. Geib; Daniel Rubinoff (Molecular Ecology, 2018)
Biological control agents have several advantages over chemical control for pest management, including the capability to restore ecosystem balance with minimal non‐target effects and a lower propensity for targets to develop resistance. These factors are particularly important for invasive species control. The coconut rhinoceros beetle ( Oryctes rhinoceros Linnaeus) is a major palm pest that invaded many Pacific islands in the early 20th century through human‐mediated dispersal. Application of the Oryctes nudivirus in the 1960s successfully halted the beetle's first invasion wave and made it a textbook example of successful biological control. However, a recently discovered O. rhinoceros biotype that is resistant to the nudivirus appears to be correlated with a new invasion wave. We performed a population genomics analysis of 172 O. rhinoceros from seven regions, including native and invasive populations, to reconstruct invasion pathways and explore correlation between recent invasions and biotypes. With dd RAD sequencing, we generated data sets ranging from 4,000 to 209,000 loci using stacks and ipyrad software pipelines and compared genetic signal in downstream clustering and phylogenetic analyses. Analysis suggests that the O. rhinoceros resurgence is mediated by the nudivirus‐resistant biotype. Genomic data have been proven essential to understanding the new O. rhinoceros biotype's invasion patterns and interactions with the original biotype. Such information is crucial to optimization of strategies for quarantine and control of resurgent pests. Our results demonstrate that while invasions are relatively rare events, new introductions can have significant ecological consequences, and quarantine vigilance is required even in previously invaded areas.

Population genomics and comparisons of selective signatures in two invasions of melon fly, Bactrocera cucurbitae (Diptera: Tephritidae) - Julian R. Dupuis; Sheina B. Sim; Michael San Jose; Luc Leblanc; M. Aftab Hoassain; Daniel Rubinoff; Scott M. Geib (Biological Invasions, 2018)

An analysis of first-time and repeat visitors to Korean national parks from 2007 and 2013 - Yunseon Choe; Michael A. Schuett; Kyu-Won Sim (Journal of Mountain Science, 2017)

Erratum to: Development of an Electromechanical Grade to Assess Human Knee Articular Cartilage Quality - Sotcheadt Sim; Insaf Hadjab; Martin Garon; Eric Quenneville; Patrick Lavigne; Michael D. Buschmann (Annals of Biomedical Engineering, 2017)

Development of an Electromechanical Grade to Assess Human Knee Articular Cartilage Quality - Sotcheadt Sim; Insaf Hadjab; Martin Garon; Eric Quenneville; Patrick Lavigne; Michael D. Buschmann (Annals of Biomedical Engineering, 2017)

Integrative taxonomy reveals too extensive lumping and a new species in the moss genus Amphidium (Bryophyta) - Manuela Sim-Sim; Olga M. Afonina; Tereza Almeida; Aurélie Désamoré; Benjamin Laenen; César Augusto Garcia; Juana M. González-Mancebo; Michael Stech (Systematics and Biodiversity, 2017)

High reactive oxygen species levels are detected at the end of the chronological life span of translocant yeast cells - Jason Sims; Carlo V. Bruschi; Chloé Bertin; Nicole West; Michael Breitenbach; Sabrina Schroeder; Tobias Eisenberg; Mark Rinnerthaler; Peter Raspor; Valentina Tosato (Molecular Genetics and Genomics, 2016)

Development of SCAR marker for the detection of QTL for resistance to dollar spot in creeping bentgrass (Agrostis stolonifera L.) - Nanda Chakraborty; Sung-Chur Sim; Michael Casler; Geunhwa Jung (Horticulture, Environment, and Biotechnology, 2014)

Transcriptional response of Pseudomonas aeruginosa to a phosphate-deficient Lolium perenne rhizosphere - Agnieszka Zyśko; Hervé Sanguin; Andrew Hayes; Leanne Wardleworth; Leo A. H. Zeef; Allan Sim; Eric Paterson; Brajesh K. Singh; Michael A. Kertesz (Plant and Soil, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

The genome of Syntrophomonas wolfei : new insights into syntrophic metabolism and biohydrogen production - Jessica R. Sieber; David R. Sims; Cliff Han; Edwin Kim; Athanasios Lykidis; Alla L. Lapidus; Erin McDonnald; Lars Rohlin; David E. Culley; Robert Gunsalus; Michael J. McInerney (Environmental Microbiology, 2010)
Summary Syntrophomonas wolfei is a specialist, evolutionarily adapted for syntrophic growth with methanogens and other hydrogen‐ and/or formate‐using microorganisms. This slow‐growing anaerobe has three putative ribosome RNA operons, each of which has 16S rRNA and 23S rRNA genes of different length and multiple 5S rRNA genes. The genome also contains 10 RNA‐directed, DNA polymerase genes. Genomic analysis shows that S. wolfei relies solely on the reduction of protons, bicarbonate or unsaturated fatty acids to re‐oxidize reduced cofactors. Syntrophomonas wolfei lacks the genes needed for aerobic or anaerobic respiration and has an exceptionally limited ability to create ion gradients. An ATP synthase and a pyrophosphatase were the only systems detected capable of creating an ion gradient. Multiple homologues for β‐oxidation genes were present even though S. wolfei uses a limited range of fatty acids from four to eight carbons in length . Syntrophomonas wolfei , other syntrophic metabolizers with completed genomic sequences, and thermophilic anaerobes known to produce high molar ratios of hydrogen from glucose have genes to produce H 2 from NADH by an electron bifurcation mechanism. Comparative genomic analysis also suggests that formate production from NADH may involve electron bifurcation. A membrane‐bound, iron–sulfur oxidoreductase found in S. wolfei and Syntrophus aciditrophicus may be uniquely involved in reverse electron transport during syntrophic fatty acid metabolism. The genome sequence of S. wolfei reveals several core reactions that may be characteristic of syntrophic fatty acid metabolism and illustrates how biological systems produce hydrogen from thermodynamically difficult reactions.

Molecular, phytochemical and morphological characterization of the liverwort genus Radula in Portugal (mainland, Madeira, Azores) - Michael Stech; Manuela Sim-Sim; M. Glória Esquível; Leena luís; Susana Fontinha; Carlos Lobo; César Garcia; Soraia Martins; Cristiana Vieira; José Barroso; Luis G. Pedro; A. Cristina S. Figueiredo (Systematics and Biodiversity, 2010)

Kinetics of omeprazole and escitalopram in relation to the CYP2C19*17 allele in healthy subjects - Staffan Ohlsson Rosenborg; Jessica Mwinyi; Maria Andersson; R. Michael Baldwin; Rasmus Steen Pedersen; Sarah C. Sim; Leif Bertilsson; Magnus Ingelman-Sundberg; Erik Eliasson (European Journal of Clinical Pharmacology, 2008)

A fatal case of iatrogenic hypercalcemia after calcium channel blocker overdose - Michael T. Sim; Frazier T. Stevenson (Journal of Medical Toxicology, 2008)

Occupational exposure to low frequency magnetic fields and the risk of low grade and high grade glioma - Ken Kyriakos Karipidis; Geza Benke; Malcolm R. Sim; Michael Yost; Graham Giles (Cancer Causes & Control, 2007)

Genetic mapping of a major gene affecting onion bulb fructan content - John McCallum; Andrew Clarke; Meeghan Pither-Joyce; Martin Shaw; Ruth Butler; Don Brash; John Scheffer; Ian Sims; Sjaak van Heusden; Masayoshi Shigyo; Michael J. Havey (Theoretical and Applied Genetics, 2006)

Blood glucose threshold and the metabolic responses to incremental exercise tests with and without prior lactic acidosis induction - Herbert Gustavo Simes; Carmen S. G. Campbell; Michael R. Kushnick; Akiko Nakamura; Christos S. Katsanos; Vilmar Baldissera; Robert J. Moffatt (European Journal of Applied Physiology, 2003)

Respiratory symptoms and lung-function changes with exposure to five substances in aluminium smelters - Lin Fritschi; Malcolm R. Sim; Andrew Forbes; Michael J. Abramson; Geza Benke; William A. Musk; Nicholas H. de Klerk (International Archives of Occupational and Environmental Health, 2003)

Respiratory symptoms and lung function in bauxite miners - Jeremy R. Beach; Nicholas H. de Klerk; Lin Fritschi; Malcolm R. Sim; A. William Musk; Geza Benke; Michael J. Abramson; John J. McNeil (International Archives of Occupational and Environmental Health, 2001)

Zinc ligand-disrupted recombinant human Endostatin: Potent inhibition of tumor growth, safety and pharmacokinetic profile - B. Kim Lee Sim; William E. Fogler; Xin Hua Zhou; Hong Liang; John W. Madsen; Kieu Luu; Michael S. O'Reilly; Joseph E. Tomaszewski; Anne H. Fortier (Angiogenesis, 1999)